PENGARUH GAYA KEPEMIMPINAN SITUASIONAL DAN KOMUNIKASI INTERNAL TERHADAP KINERJA PENDIDIK KELOMPOK BERMAIN KECAMATAN BABADAN KABUPATEN PONOROGO - Agustiana, Wiwik; Rispantyo, Rispantyo; Sriwidodo, Untung (JURNAL MANAJEMEN SUMBER DAYA MANUSIA, 2019)
Play Group (KB) is an initial education level that prepares students for higher education levels such as TK / RA, SD / MI. The success of the Play Group (KB) education will contribute greatly to the development of students in the future. Of the 50 educators in the Play Group, there is a large majority (62%) educators in the Play Group in Babadan Sub district, Ponorogo Regency in teaching are not equipped with a daily work plan (RKH) in advance so that it will have an impact on the implementation of unplanned teaching and learning interactions and tends to ignore the assessment student achievement. The attention of most managers to educators such as internal communication has not been carried out to the fullest due to the rush of other tasks. This type of research is quantitative conducted on 21 Play Groups (KB) in Babadan District, Ponorogo Regency. The population and sample are all educators in the Play Group (KB) in the Babadan Sub district of Ponorogo Regency, amounting to 50 people. The independent variable is situational leadership and internal communication. The dependent variable is teacher performance. Data Quality Test with validity and reliability. Data analysis with Multiple Linear Regression, t test, F test and Coefficient of Determination. The results showed that all educators were female, 46% were aged 20-30 years, most (64%) had an undergraduate education and most (58%) had less than 5 years of service. Situational Leadership has positive but not significant effect on Teacher Performance, Internal Communication has positive and significant effect on Teacher Performance in Babadan Subdistrict, Ponorogo District. It is recommended that managers improve situational leadership so that a harmonious working atmosphere will be created.